Effects of gastrointestinal inflammation on enteroendocrine cells and enteric neural reflex circuits - Lomax, Alan E.; Linden, David R.; Mawe, Gary M.; Sharkey, Keith A. (Autonomic neuroscience, 2006)
Inflammation of the gastrointestinal (GI) tract has pronounced effects on GI function. Many of the functions of the GI tract are subject to neural regulation by the enteric nervous system (ENS) and its extrinsic connections. Therefore, it is possible that inflammatory effects on the ENS contribute to altered function during GI inflammation. The reflex circuitry of the ENS is comprised of sensory transducers in the mucosa (enteroendocrine cells), afferent neurons, interneurons and motor neurons. This review focuses on recent data that describe inflammation-induced changes to the ENS and mucosal enteroendocrine cells. Studies of tissues from patients with inflammatory bowel disease (IBD) and from animal models of IBD have demonstrated marked changes in mucosal enteroendocrine cell signaling. These changes, which have been studied most intensely in 5-HT-containing enterochromaffin cells, involve changes in the number of cells, their signaling molecule content or their means of signal termination. Morphological evidence of enteric neuropathy during inflammation has been obtained from human samples and animal models of IBD. The neuropathy can reduce the number of enteric neurons in the inflamed region and is often accompanied by a change in the neurochemical coding of enteric neurons, both in the inflamed region and at distant sites. Electrophysiological recordings have been made from enteric neurons in inflamed regions of the colon of animal models of IBD. These studies have consistently found that inflammation increases excitability of intrinsic primary afferent neurons and alters synaptic transmission to interneurons and motor neurons. These data set the stage for a comprehensive examination of the role of altered neuronal and enteroendocrine cell signaling in symptom generation during GI inflammation.